PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA KANTOR PT. CEMERLANG SURYA GEMILANG MAKASSAR - Basri, Basri; Hamris, Saddiya (Jurnal Metaverse ADPERTISI, 2024)
The purpose of this research is to determine and analyze the influence of leadership style and organizational culture on employee performance at the PT office. Cemerlang Surya Gemilang Makassar partially and simultaneously. This type of research uses a quantitative descriptive approach with a population that will be sampled as 85 people, with a sampling technique using a saturated sample, that is, the entire population will be used as a sample. The analytical method used is multiple linear regression analysis with hypothesis testing using the partial t test, simultaneous F test and determination test (R2). The research results obtained are (1) Leadership style has a positive and insignificant effect on employee performance at PT offices. Cemerlang Surya Gemilang (2) Organizational culture has a positive and significant effect on employee performance at the PT office. Cemerlang Surya Gemilang, (3) Leadership style and organizational culture have a positive and significant effect on employee performance at the PT office. Brilliant Surya Gemilang. Organizational culture has a dominant influence on improving employee performance at the PT office. Brilliant Surya Gemilang